HUBUNGAN KEBIASAAN CUCI TANGAN, MENGELOLA AIR MINUM DAN MAKANAN DENGAN STUNTING DI SULAWESI TENGAH - Syam, Dedi Mahyudin; Sunuh, Herlina S (Gorontalo Journal of Public Health, 2020)
Environmental factors, birth weight and food intake can influence the incidence of stunting. The prevalence of stunting in toddlers in Central Sulawesi Province in 2015 was very short by 11.4% and short by 23.9%. 2-16 very short categories by 10.2% and short categories by 21.8%. 2017 the very short category was 14.0% and the short category was 22.1%. The purpose of this research was to know handwashing with soap, treating drinking water and food related to stunting in Central Sulawesi. The type of research was analytic with the approach of cross sectional survey with a sample 289 people in 4 (four) Regency Areas (Banggai, Donggala, Sigi and Palu). Data processing and analysis include univariate and bivariate were used chi square test. Results of 289 respondents carry out handwasing with soap 176 (60.9%), not carry out handwasing with soap activity 113 (39.1%), statistical test obtained p value = 0.000. Treating drinking water and food 270 (93.4%), not treating clean water and food only 19 (6.6%), stunting status 133 (46.0%), not stunting 155 (56.0%), statistical test obtained p value = 0.001. Conclusion There was a relationship between hand washing with soap, treating drinking water and food with stunting in Central Sulawesi.Faktor lingkungan, berat badan lahir dan asupan makanan dapat mempengaruhi kejadian stunting. Prevalensi stunting pada balita di Provinsi Sulawesi Tengah tahun 2015 kategori sangat pendek sebesar 11.4% dan pendek sebesar 23.9%. 2-16 kategori sangat pendek sebesar 10.2% dan kategori pendek sebesar 21,8%. 2017 kategori sangat pendek sebesar 14.0% dan kategori pendek sebesar 22.1%. Tujuan penelitian adalah diketahuinya cuci tangan pakai sabun (CTPS), mengelola air minum dan makanan berhubungan  dengan stunting di Sulawesi Tengah. Jenis penelitian adalah analitik dengan pendekatan cross sectional survey dengan sampel berjumlah 289 orang di 4 (empat) daerah Kabupaten (Banggai, Donggala, Sigi dan Palu). Pengolahan dan analisis data meliputi univariat, Bivariat menggunakan uji chi square. Hasil penelitian menunjukkan dari 289 responden melaksanakan CTPS 176 (60,.9%), tidak CTPS 113 (39,1%), Uji statistik diperoleh nilai p = 0,000. Sudah mengelola air minum dan makanan 270 (93,4%), tidak mengelola air bersih dan makanan 19 (6,6%), status gizi stunting 133 (46,0%), tidak stunting 155 (56,0%), uji statistik diperoleh nilai p = 0,001. Kesimpulan ada hubungan cuci tangan pakai sabun, pengelolaan air minum dan makanan dengan stunting di Sulawesi Tengah.